400-nm InGaN-GaN and InGaN-AlGaN multiquantum well light-emitting diodes - Chang, S.J.; Kuo, C.H.; Su, Y.K.; Wu, L.W.; Sheu, J.K.; Wen, T.C.; Lai, W.C.; Chen, J.R.; Tsai, J.M. (IEEE journal of selected topics in quantum electronics, 2002)
The 400-nm In/sub 0.05/Ga/sub 0.95/N-GaN MQW light-emitting diode (LED) structure and In/sub 0.05/Ga/sub 0.95/N-Al/sub 0.1/Ga/sub 0.9/N LED structure were both prepared by organometallic vapor phase epitaxy. It was found that the use of Al/sub 0.1/Ga/sub 0.9/N as the material for barrier layers would not degrade crystal quality of the epitaxial layers. It was also found that the 20-mA electroluminescence intensity of InGaN-AlGaN multiquantum well (MQW) LED was two times larger than that of the InGaN-GaN MQW LED. The larger maximum output intensity and the fact that maximum output intensity occurred at larger injection current suggest that AlGaN barrier layers can provide a better carrier confinement and effectively reduce leakage current.